Populismi e futuro della democrazia in Europa. Una riflessione sulle orme di Dahrendorf - Raffini, Luca (SocietàMutamentoPolitica, 2019)
The article proposes a critical reading of contemporary populisms in the footsteps of Ralf Dahrendorf’s thought. Neoliberal globalization has been accompanied – for a significant part of citizenship – by a reduction in life chances, as a consequence of a model of development that has increasingly tended to place the emphasis on economic development at detriment of political freedom and social equity. On the political side we have witnessed the development of a novel kind of technocratic and scarcely democratic governance. We explore how the de-legitimization of institutions and traditional political actors and the worsening of the life condition promoted the rise of populist and anti-establishment movements. Populism expresses an view of democracy which stress the principle of popular sovereignty to the detriment of the rule of law and denies, or minimizes, the existence of a plurality of legitimate conflicting interests and opinions. According to Dahrendorf legacy, the rise of populism can be read as the expression of an ambiguous and dangerous phase of transformation of democracy. It represents, in its main expressions, a model of post-liberal democracy that can nevertheless feed risky forms of democratic authoritarianism.